Notification of crop varieties and registration of germplasm : Bread Wheat, Variety DBW 110 - Singh, S.K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Wheat is one of the major rabi crop in the central zone of Indian wheat belt where wheat is grown in warmer climatic conditions due to limited water availability and higher temperatures during crop period. Under these conditions, wheat is exposed to early and terminal heat stress conditions and limited water availability as major abiotic factors. The brown and black rusts are also crucial biotic stresses that affect wheat yields. Keeping this in view, Wheat improvement for warmer areas programme was initiated at IIWBR (Earlier DWR), Karnal which resulted in development of wheat variety DBW 110.